Analisis Kelayakan Kepahlawanan Soeharto Berdasarkan UU 20/2009 dan Standar Hak Asasi Manusia Modern - Andreas Masaroni; Bonifasius Sola; Eduard. Risky Mayokan; Kristovel Ivan Pepende; Marco Yohanis Mamarodia; Antonius Baju Nujartanto (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
The awarding of the title National Hero to Soeharto through Presidential Decree No. 116/TK/2025 has generated public debate. On the one hand, Soeharto is regarded as having made significant contributions through political stability, economic growth, and development programs such as the Repelita, which brought substantial improvements to public welfare. On the other hand, his period of rule was also marked by serious human rights violations. This study aims to assess Soeharto’s eligibility to receive the title of National Hero based on Law No. 20 of 2009 and modern human rights standards, particularly the principles of non-derogable rights, accountability, and human dignity. The fundamental assumption of this study is that a hero’s title is not merely a historical judgment, but also a moral one that must comply with national legal standards and universal norms, and must be free from violations of absolute human rights. The analysis finds that although Soeharto achieved major accomplishments in national development, the structural involvement of the state in human rights violations during his presidency violates fundamental moral principles and the criteria for heroism as stipulated in Law No. 20 of 2009. Therefore, the granting of the National Hero title to Soeharto is ethically and legally highly problematic.